Pengaru Komunikasi Organisasi Terhadap Kualitas Pelayanan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sinjai - Amal, Suci; Mahsyar, Abdul; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study was to determine the effect of organizational communication on service quality in the population and civil registration department of Sinjai Regency. The research method used in this study is a quantitative research method with descriptive type. Data were obtained from 95 respondents from 1800 population in 1 month, while the sample used was cluster random sampling. Data analysis technique used is a simple linear regression analysis method with Y = 19,711 + 0,489X with the help of Pearson product moment (r) through the SPSS Version 22.0 program at α = 0.05 level. The results showed that there was a significant positive effect between organizational communication on service quality in the population and civil registration office in Sinjai district by 11.8% with a regression coefficient of 0.357 in the interpretation of the regression coefficient in the medium category so that it can be said that there was an influence of organizational communication on service quality in the service demography and civil registration of Sinjai Regency.